2014
DOI: 10.1016/j.clcc.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Signature in Metastatic Colorectal Cancer Patients Treated With Anti-EGFR Monoclonal Antibodies

Abstract: The MiR-99a/Let-7c/miR-125b signature may improve the selection of patients with KRAS wild-type mCRC as good candidates for anti-EGFR therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…This difference also further enhances Wnt activity and may form a feedback loop as a downstream target of Wnt 191 . [164][165][166][167] MiR-126 ↓ Decreased sensitivity to capecitabine and oxaliplatin (XELOX) [168][169] MiR-31 ↑ Decreased sensitivity to 5-fluorouracil …”
Section: Colon Cancer-associated Transcript (Ccat2)mentioning
confidence: 99%
See 1 more Smart Citation
“…This difference also further enhances Wnt activity and may form a feedback loop as a downstream target of Wnt 191 . [164][165][166][167] MiR-126 ↓ Decreased sensitivity to capecitabine and oxaliplatin (XELOX) [168][169] MiR-31 ↑ Decreased sensitivity to 5-fluorouracil …”
Section: Colon Cancer-associated Transcript (Ccat2)mentioning
confidence: 99%
“…These factors are important in predicting the response to particular therapies. MicroRNAs act as positive biomarkers indicating sensitivity to therapy or as negative biomarkers signifying resistance to treatment and assisting in choosing the appropriate treatment regimen (Table 1) [164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179] .…”
Section: Therapeutic Biomarkersmentioning
confidence: 99%
“…Regardless, whereas such assays may prove useful for predicting chemotherapeutic response in patients with stage II miRNA profiles have also been evaluated for their ability to predict response to anti-EGFR therapy. A panel consisting of miR-99a, Let-7c, and miR-125b was found to predict enhanced progression-free survival and overall survival after treatment with anti-EGFR mAbs in patients with WT KRAS [64]. Low miR-181a was shown to correlate with poor survival in patients with KRAS-WT CRC after treatment with EGFR-targeting mAbs [65], whereas differential miR-31-3p levels were also shown to predict response [66].…”
Section: Micrornasmentioning
confidence: 95%
“…In patients with KRAS mutations, those with high levels of hepatocyte growth factor (HGF) or epiregulin (EREG) have shorter progression-free survival and overall survival compared with those with low levels of HGF or EREG (Takahashi et al 2014 ). One study has explored miRNAs as biomarkers of response to anti-EGFR MAbs and found that MiR-99a/Let-7c/miR-125b signature may improve the selection of patients with KRAS wild-type mCRC as good candidates for this therapy (Cappuzzo et al 2014 ).…”
Section: Chemogenomic Approach To Drug Resistancementioning
confidence: 97%